Meningioma in Focus: Charting the Terrain of Imaging, Grading, and Pathological Vistas - Salehi, Ali; Mohammad khani Pordanjani, Behrooz; Bidari Zerehpoosh, Farahnaz; Moosavizadeh, Fatemeh; Haghighimorad, Maryam (Novelty in Biomedicine, 2024)
Background: Meningiomas constitute a significant proportion of primary intracranial tumors, demanding a nuanced understanding of their radiological features for informed clinical decisions. This prospective study aimed to explore the intricate relationship between magnetic resonance imaging (MRI) findings and the pathological grade of meningiomas to provide insights into their diverse characteristics. Materials and Methods: A cohort of 52 meningioma patients underwent comprehensive MRI evaluations. The study encompassed various aspects of tumor radiology, including location, peritumoral edema severity, tumor margin distinctiveness, bone infiltration, adjacent bone reaction, apparent diffusion coefficient (ADC) patterns, intratumoral calcifications, bleeding within the tumor, vascularization, and tumor enhancement. Results: The analysis revealed that 73.1% of patients presented with grade 1 meningioma, while 26.9% exhibited grade 2 tumors, with no grade 3 cases detected. Intriguingly, while age and gender did not significantly differ between grades, several MRI findings demonstrated noteworthy distinctions. Grade 2 meningiomas were associated with moderate to severe peritumoral edema, indistinct tumor margins, increased vascularization, and heterogeneous tumor enhancement patterns. Notably, logistic regression analysis indicated that none of the investigated radiological parameters independently predicted the pathological grade of meningioma. Conclusion: These findings emphasize the need for a comprehensive meningioma assessment approach, integrating radiological insights into clinical decision-making and prognosis for enhanced patient care.